GAMBARAN SANITASI PEMUKIMAN DI DESA ROWOREJO KECAMATAN NEGERI KATON KABUPATEN PESAWARAN TAHUN 2020 - Melani, Dian Septi; Ahyanti, Mei; Ginting, Daria Br (Poltekkes Kemenkes Tanjung Karang, 2021)
An unhealthy environment can lead to environmental-based disease transmission. Based on the preliminary survey, many houses still do not meet health requirements, such as having no ceiling, closed sewerage, and no latrine. This study aims to determine the description of residential sanitation, including the components of the house, the components of sanitation facilities, and the occupants' behavior. This research is descriptive with the survey method. The population is all houses in Roworejo Village, as many as 1,244 houses. Data collection is done by visiting people's homes, conducting an assessment using a checklist guide. Interviews were conducted to support the required data. The data that has been collected is scored, processed with a computer program, and presented in tabular form. The results of the study found that the majority of the sanitation components had met the requirements. However, there are still physical components of the house (30%), components of sanitation facilities (34%), and unhealthy behavior of residents (30%). Increasing public knowledge is an action that must be taken in order to change public health behavior.